1986
DOI: 10.1136/thx.41.5.386
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow during cardiopulmonary bypass in man: effect of arterial filtration.

Abstract: Cerebral blood flow was recorded in 39 patients undergoing cardiac surgery by intraarterial injection of xenon 133. There were three subgroups of patients: 10 patients had a 20 micron arterial filter (Johnson) and 11 a 40 micron filter (Pall), and 18 had no arterial filtration. All patients had a 40 micron (Pall) filter in the coronary suction line. Significant changes in cerebral blood flow occurred during extracorporeal circulation (p < 0.0001). For all patients cerebral blood flow increased from a resting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…28 Otherwise, Henriksen et al . 29 found that the use of arterial filtration only modestly reduced the cerebral hyperemic response to bypass, which they had previously attributed to microembolization. Blauth et al .…”
Section: Discussionmentioning
confidence: 84%
“…28 Otherwise, Henriksen et al . 29 found that the use of arterial filtration only modestly reduced the cerebral hyperemic response to bypass, which they had previously attributed to microembolization. Blauth et al .…”
Section: Discussionmentioning
confidence: 84%
“…However, those studies whose outcomes are clinical should ideally have a more strictly defined selection criteria. For example, Henriksen and Hjelms, 14 Sellman et al 15 and Taggart et al 11 investigated cerebral blood flow, magnetic resonance imaging (MRI) brain changes and S100b levels, respectively. Since they were all measuring outcomes related to the brain and brain injury, they all excluded from their study population patients with a history of cerebrovascular disease.…”
Section: Results Of Searchmentioning
confidence: 99%
“…Experimental evidence confirms the benefit of selective antegrade cerebral perfusion compared to retrograde perfusion and hypothermic circulatory arrest [72]. The effect of arterial filtration on cerebral auto-regulation [73,74] and the choice of pH management [75] has also been addressed. A combined experimental and computational approach may have a role to play with the optimisation of cerebral blood flow on cardiopulmonary bypass in terms of a reduction in neurological events [76,77].…”
Section: Discussionmentioning
confidence: 99%